2011
DOI: 10.1242/jcs.087718
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of naïve and genetically modified HLA-class-I-knockdown human embryonic stem cells

Abstract: KD was followed by flow cytometry and showed levels between 1% and 12% of those of naïve hESC between days 7 and 42 (means ± s.e.m.). (b) A total of 10 6 hESCs or hESC KD were transplanted into the gastrocnemius muscle of either immunocompetent Balb/c or severely immunocompromised SCID-beige mice. All ten Balb/c mice rapidly rejected the hESC transplants, whereas the cells survived in ten SCID-beige recipients. Rejection of hESC KD was markedly attenuated and four out of ten hESC KD grafts achieved long-term s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 60 publications
1
28
0
Order By: Relevance
“…The induction of immune tolerance via the transplantation of human ESC-derived dendritic cells has also been suggested as a possibility [188]. Another strategy to evade T-cell activation is through the knockdown of HLA-class I proteins as shown with human ESC xenotransplants into mice [189]. Lu and colleagues disrupted β-2 microglobulin in human ESCs and generated a cell line that has impaired surface expression of HLA-class I proteins [190].…”
Section: Remaining Obstacles To the Successful Translation Of Plurmentioning
confidence: 99%
“…The induction of immune tolerance via the transplantation of human ESC-derived dendritic cells has also been suggested as a possibility [188]. Another strategy to evade T-cell activation is through the knockdown of HLA-class I proteins as shown with human ESC xenotransplants into mice [189]. Lu and colleagues disrupted β-2 microglobulin in human ESCs and generated a cell line that has impaired surface expression of HLA-class I proteins [190].…”
Section: Remaining Obstacles To the Successful Translation Of Plurmentioning
confidence: 99%
“…Manipulation of HLA expression on stem cells has recently shown promise as a strategy for generating hypoimmunogenic grafts. 41 The same strategy has been previously used to facilitate transplantation of hematopoietic stem cells (HSCs). 42 The clinical applicability of this strategy, however, remains questionable, as it requires genetic manipulation to knock down a gene, and may lead to the introduction of genetic variations.…”
Section: Immunogenic Molecules Of Pluripotent Stem Cellsmentioning
confidence: 99%
“…Furthermore, xenotransplantation of human embryonic stem cells (hESC) induces a rapid surge of DSA-HLA-I that contribute to immune rejection, whereas HLA-I knockdown remarkably alleviates antibody production and prolongs the survival of hESC24. Although the mechanisms involved in humoral allo-rejection of stem cells are still unknown, studies in animal model suggested that CDC and ADCC might be responsible for stem cell elimination in vivo, as in the case of organ or cell transplantations25.…”
mentioning
confidence: 99%